The GSI-UNILAC - a megawatt beam injector for FAIR - Barth, W.; Dahl, L.; Groening, L.; Yaramyshev, S. (Вопросы атомной науки и техники, 2006)
For the FAIR project the present GSI accelerator complex, consisting of the heavy ion high current linac UNILAC and the synchrotron SIS 18, is foreseen to serve as an injector for up to 10¹² U²⁸⁺ particles/s. Different hardware measures and careful fine tuning in all sections of the UNILAC resulted in an increase of the beam intensity to 10¹¹ U²⁸⁺-ions or 2×10¹⁰ U⁷³⁺-ions per 100 μs. Further upgrade measures are described. Представлен GSI усилительный комплекс, состоящий из сильноточного линейного ускорителя тяжелых ионов UNILAC и синхротрона SIS 18, который предназначен для работы в качестве инжектора до10¹² U²⁸⁺ частиц/с проекта FAIR. Различные измерения аппаратуры и тщательная тонкая настройка всех секций UNILAC привели к увеличению интенсивности пучка до 10¹¹ U²⁸⁺-ионов или 2×10¹⁰ U⁷³⁺ -ионов на 100 мкс. Описана его дальнейшая модернизация. Представлено GSІ підсилювальний комплекс, що складається з потужнострумового лінійного прискорювача важких іонів UNІLAC і синхротрона SІS 18, що призначений для роботи як інжектор до 10¹² U²⁸⁺ часток/c проекту FAІR. Різні виміри апаратури і ретельне тонке настроювання всіх секцій UNІLAC привели до збільшення інтенсивності пучка до 10¹¹ U²⁸⁺-іонів або 2×10¹⁰ U⁷³⁺-іонів на 100 мкс. Описана його подальша модернізація.